Feasibility of clinical target volume reduction for glioblastoma treated with standard chemoradiation based on patterns of failure analysis. (April 2023) - Minniti, Giuseppe; Tini, Paolo; Giraffa, Martina; Capone, Luca; Raza, Giorgio; Russo, Ivana; Cinelli, Elisa; Gentile, PierCarlo; Bozzao, Alessandro; Paolini, Sergio; Esposito, Vincenzo
Abstract: Purpose: To analyze recurrence patterns in patients with glioblastoma (GBM) after standard chemoradiation according to different target volume delineation strategies. Methods and materials: Two hundred seven patients with GBM who recurred after standard chemoradiation were evaluated. According to ESTRO target volume delineation guideline, the CTV was generated by adding a 2-cm margin to the GTV, defined as the resection cavity plus residual tumor. Patterns of failure were analyzed using dose-volume histogram. Recurrent lesions were defined as in-field, marginal, or distant if > 80 %, 20–80 %, or < 20 % of the intersecting volume was included in the 95 % isodose line. For each patient, a theoretical plan consisting of reduced 1-cm GTV-to-CTV margin was created to compare patterns of failure and radiation doses to normal brain. Results: Median overall survival and progression-free survival times were 15.3 months and 7.8 months, respectively, from the date of surgery. Recurrences were in-field in 180, marginal in 5, and distant in 22 patients. According to MGMT promoter methylation, distant recurrences occurred in 18.6 % of methylated and 6 % of unmethylated tumors ( p  = 0.0046). Following replanning with 1-cm reduced margin, dosimetric analysis showed similar patterns of failure. Recurrences were in-field, marginal, and distant in 177, 3, and 27 plans, respectively, although radiation doses to the healthy brain and hippocampi were significantly lower compared with standard target delineation ( p  = 0.0001). Conclusion: Current provide the rationale for evaluating GTV-to-CTV margin reduction in future clinical trials with the aim of limiting the cognitive sequelae of GBM irradiation while maintaining survival benefits of standard chemoradiation.